2017
DOI: 10.1186/s12939-017-0678-8
|View full text |Cite
|
Sign up to set email alerts
|

Lookism hurts: appearance discrimination and self-rated health in South Korea

Abstract: BackgroundDespite a growing body of evidence suggesting that discrimination harms health, the association between appearance discrimination and health has been understudied. Our study investigated the association between perceived appearance discrimination and self-rated health among emerging adults using a nationally representative cohort study in South Korea.MethodsWe analyzed the 2nd-10th (2005–2013) waves of cohort data from the Korean Education Employment Panel (KEEP). KEEP consists of two groups of indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
0
8
0
2
Order By: Relevance
“…The negative correlates of body-related discrimination do not end in adolescence. In adulthood, individuals who have experienced discrimination based on their appearance report worse self-rated health (Lee, Son, Yoon, & Kim, 2017) and lower well-being (Sutin, Stephan, Carretta, & Terracciano, 2015).…”
mentioning
confidence: 99%
“…The negative correlates of body-related discrimination do not end in adolescence. In adulthood, individuals who have experienced discrimination based on their appearance report worse self-rated health (Lee, Son, Yoon, & Kim, 2017) and lower well-being (Sutin, Stephan, Carretta, & Terracciano, 2015).…”
mentioning
confidence: 99%
“…In turn, a study by Sulaimani et al showed that persons suffering from autism are also subject to discrimination; however studies of this problem are scarce [40]. This problem still requires many more studies in order to confirm the relationship between discrimination and the state of health [41,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that young people have a higher level of media involvement than other age groups, and that the higher the level of media involvement, the higher the desire for cosmetic surgery, value attributed to cosmetic surgery, and attitudes toward risk tolerance [ 34 ]. Eastern cultures, such as that of Korea, tend to pursue Western face and body shapes as beauty standards, emphasizing certain features such as double eyelids, V-shaped faces, and voluptuous breasts [ 35 ]. Adolescents may encounter psychological difficulties such as low self-esteem, appearance stress, and depression if they feel that they must change their appearance to be accepted or valued by their peers or society [ 4 ].…”
Section: Discussionmentioning
confidence: 99%